2016
DOI: 10.1186/s12986-016-0095-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolic biomarkers distinguish metabolically healthy peripherally obese from unhealthy centrally obese individuals

Abstract: BackgroundMetabolic abnormalities are more associated with central obesity than peripheral obesity, but the underlying mechanisms are largely unknown. The present study was to identify serum metabolic biomarkers which distinguish metabolically unhealthy centrally obese (MUCO) from metabolically healthy peripherally obese (MHPO) individuals.MethodsA two-stage case–control study design was employed. In the discovery stage, 20 individuals (10 MHPO and 10 MUCO) were included and in the following validation stage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 72 publications
5
46
1
1
Order By: Relevance
“…Also, when we evaluated the insulin resistance, we found that MHO had significantly lower HOMA index compared to MSO patients, and that MHO and MHNO did not differ with respect to insulin sensibility. Similar results have been published in metabolically healthy peripherally obese [30]. …”
Section: Discussionsupporting
confidence: 91%
“…Also, when we evaluated the insulin resistance, we found that MHO had significantly lower HOMA index compared to MSO patients, and that MHO and MHNO did not differ with respect to insulin sensibility. Similar results have been published in metabolically healthy peripherally obese [30]. …”
Section: Discussionsupporting
confidence: 91%
“…Although these observations suggest that iron and glucose or lipid homeostasis interact at the molecular level, data on the site of these interactions have remained scarce in humans. Profiling of the serum metabolome has been used as a valuable tool to identify subtle changes in various diseases such as cancer, cardiovascular diseases, or obesity [43], [44], [45].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics, or the systematic and comprehensive study of low molecular weight compounds in biological tissues and fluids, has emerged as a powerful tool to refine our knowledge of more nuanced differences in metabolic phenotypes. To date, a handful of small studies in adults have used metabolomics to characterize differences in circulating metabolites that differ between metabolically healthy versus metabolically unhealthy obesity in adult populations . These studies have identified differences in compounds on branched‐chain amino acid (BCAA) and lipid metabolism pathways between metabolically healthy versus unhealthy obesity.…”
Section: Introductionmentioning
confidence: 99%